PENGARUH PENDAPATAN ASLI DAERAH DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2013-2017 - Hasna Lathifa; Haryanto Haryanto (Diponegoro Journal of Accounting, 2019)
This study aims to determine the effect of local own-source revenue and capital expenditure on the financial performance of local government on regencies/cities in Central Java Province 2013-2017. This research is important to do because it can provide information about the effect of local own-source revenue and capital expenditure on the financial performance of local government on regencies/cities in Central Java Province.This study was conducted by documentation method by collecting data obtained through BPK representative of Central Java Province. The data used is secondary data, which consists of the budget realization report in Central Java Province. This research use Multiple Linear Regression Method in SPSS software.The results showed that: (1) local own-source revenue has positive effect on the financial performance of local government and (2) capital expenditure has has positive effect on the financial performance of local government.